STRATEGI KOMUNIKASI PEMASARAN SENTRA TENUN PRAILIU DALAM MENINGKATKAN PENJUALAN KAIN TENUN SUMBA TIMUR - Rambu Babang, Ririn; Rachmad Rinata, Asfira (Jurnal Komunikasi Nusantara, 2019)
Woven fabric is a handicraft product inherited from generation to generation. Woven fabric can be weared as dress in dances at parties or in traditional events. Every motif on woven fabric has meaning both traditionally and culturally. The purpose of this study is to find out the marketing strategy and the factors that influence it. The method used in this research is descriptive qualitative method with data collection techniques using the method of interview, observation, documentation to obtain primary data and secondary data. As well as data analysis techniques carried out through reduction, presentation and drawing conclusions. The result shows that implementation of marketing communication strategies Prailiu Weaving Center uses a marketing mix consisting of product, price, place and promotion which includes sales promotion, face-to-face promotion and direct marketing. The marketing strategy of the Prailiu Weaving Center consists of marketing strategy analysis which includes opportunity analysis and competitive analysis, as well as the marketing process which consists of determining product segmentation, targeting and positioning. Factors that influence marketing activities consist of supporting factors and inhibiting factors from both internal and external environments.